Implementasi Program Indonesia Pintar bagi Siswa Tingkat Sekolah Dasar - Bobby Rahman; Romi Asmara (Asia-Pacific Journal of Public Policy, 2020)
This study aims to observe closely the implementation of the Smart Indonesia Program at an elementary school in Lhokseumawe city and the obstacles encountered in its implementation. A qualitative descriptive was employed to obtain data through interviews, observation, and documentation. The results revealed that the assistance provided to students is very useful, even though only in the amount of Rp. 450,000, but it can ease the strain on parents, which is used to meet student needs. The Smart Indonesia Program is expected to be sustained so that students can continue their studies to higher levels of education. However, the obstacle faced is that the supervision from the local government (stakeholder) has not been effective. Some students cannot afford to have not been registered as recipients of the Smart Indonesia Card even though the school operator has submitted it through the Dapodik application. As a result, some parents of students complained to the school regarding this case.